Antidepressant and antipsychotic side-effects and personalised prescribing: a systematic review and digital tool development - Pillinger, T; Howes, OD; Correll, CU; Leucht, S; Huhn, M; Schneider-Thoma, J; Gaughran, F; Jauhar, S; McGuire, PK; Taylor, DM; Young, AH; McCutcheon, RA (Elsevier, 2023)
Background Side-effects of psychiatric medication impair quality of life and functioning. Furthermore, they contribute to morbidity, mortality, stigma, and poor treatment concordance resulting in relapse of psychiatric illness. Guidelines recommend discussing side-effects with patients when making treatment decisions, but a synthesis of antidepressant and antipsychotic side-effects to guide this process is missing, and considering all side-effects is a complex, multidimensional process. We aimed to create comprehensive databases of antipsychotic and antidepressant side-effects, and a digital tool to support database navigation.